An international perspective on improving occupational conditions for direct care workers in home health - Miriam Ryvicker (BMC, 2018)
Abstract The occupational health and safety of direct care workers in the home health setting has been the focal point of a somewhat scarce, though highly important, body of research. Although the demand for home care services continues to expand with the rapidly growing population of older adults worldwide, home care workers - such as home health aides and personal care attendants - do not have the same level of protections by workplace safety policies such as those implemented in hospitals and nursing homes. This commentary synthesizes international perspectives on the occupational health and safety of home care workers, including the problem of workers' rights violations and abuse by clients and their families. Prior policy and practice efforts have focused on improving the training, supervision, job satisfaction, and retention of home care workers, but have focused less on addressing issues of abuse. This paper recommends potential strategies to be developed and tested to provide a stronger support system for home care workers, more fully integrate them into the care team, and improve the occupational health and safety of this diverse, rapidly expanding workforce.